Prefeasibility techno-economic analysis of hybrid renewable energy system - Pujari Harish Kumar; R Reshma Gopi; R Rajarajan; N B Vaishali; K Vasavi; Sunil Kumar P (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
The feasibility of a hybrid renewable energy system for long-term rural electrification in Billerahalli village, Karnataka, India, is investigated in this paper. This paper presents a systematic methodology for planning and designing of an efficient hybrid system that incorporates techno-economic optimization analysis. Using HOMER PRO software, several hybridization situations are modelled and analyzed. In this design, electrolyzer and a hydrogen tank are included to reduce the need for batteries. The results shown that the optimal configuration system is a wind turbine, electrolyzer, hydrogen tank, converter, and LL1500-W battery (4 units of 800 kW/ 100 kW/ 100 kg/ 734 kW/ 500 units), with a low net present cost, cost of energy, a significant return on investment, and reductions in carbon emissions. This system offers a steady power supply by utilizing 100 % renewable sources, with a net present cost of $5.21 million and a relatively low energy cost of $0.25 per kilowatt-hour. The optimized hybrid system outperforms other system configurations in terms of cost-effectiveness and environmental performance. Concurrently, the sensitivity analysis emphasizes the system costs majorly depends on the unpredictability of solar radiation and wind speed, as well as changes in interest rates impacting future investment decisions. Finally, the study expects to provide the awareness of renewable energy potential usage in Billerahalli village and significant information for the efficient design and exploitation of hybrid renewable energy systems within the larger energy sector.